2015
DOI: 10.1159/000437235
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Citrate Inhibits Endoplasmic Reticulum Stress in Rats with Adenine-Induced Chronic Renal Failure

Abstract: Background/Aims: Endoplasmic reticulum stress (ERS) is an important self-protective cellular response to harmful stimuli that contribute to various diseases, including chronic renal failure (CRF). Sodium citrate plays an important role in antioxidant and cellular immunity, but whether it improves ERS in CRF is unclear. Methods: The rats were randomly divided into five groups: the control group, the sodium citrate control group, the model group, model rats with low dose sodium citrate (216 mg/kg), and model rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The kidney tissues of CRF rats showed severe renal injury marked by severe interstitial inflammatory cell infiltration, tubular dilation and atrophy, as well as fibrosis. These results indicate that the rat model exhibited the typical pathological features associated with CRF, which were consistent with previous studies 32, 33 . The severity of renal injury in rats with CRF was significantly ameliorated by treatment with H 2 S.
Figure 5Effects of H 2 S on morphological changes in the kidney of CRF rats.
…”
Section: Resultssupporting
confidence: 93%
“…The kidney tissues of CRF rats showed severe renal injury marked by severe interstitial inflammatory cell infiltration, tubular dilation and atrophy, as well as fibrosis. These results indicate that the rat model exhibited the typical pathological features associated with CRF, which were consistent with previous studies 32, 33 . The severity of renal injury in rats with CRF was significantly ameliorated by treatment with H 2 S.
Figure 5Effects of H 2 S on morphological changes in the kidney of CRF rats.
…”
Section: Resultssupporting
confidence: 93%
“…Both of them are almost insoluble, can precipitate in kidneys (the white dots seen in the kidney in the present study could be the precipitation of them), and then cause renal function damage [14]. Therefore, adenine is a common tool compound to establish animal model of renal failure [15]. The present study found that adenine (400 mg/kg per day for 5 days) was able to result in renal function damage and abnormal micromorphological changes with BUN and creatinine in serum increasing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, citrate inhibits urinary stones by reduced calcium stone formation in human . Our former study demonstrates that citrates influence the endoplasmic reticulum stress and immune system in the rat model of CRF . However, there has been no study about the effect of citrate on VC in CRF.…”
Section: Discussionmentioning
confidence: 91%
“…To detect the effect of citrate on renal failure, we used adenine to establish a chronic renal failure rat model. According to our former research, we selected 216 mg/kg and 746 mg/kg to be the treatment concentration of citrates . The blood was collected and the concentrations of BUN, Scr, calcium, and phosphorus were examined among different groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation